Identification of stage I/II melanoma patients at high risk for recurrence using a model combining clinicopathologic factors with gene expression profiling (CP-GEP). (March 2023) - Amaral, Teresa; Sinnberg, Tobias; Chatziioannou, Eftychia; Niessner, Heike; Leiter, Ulrike; Keim, Ulrike; Forschner, Andrea; Dwarkasing, Jvalini; Tjien-Fooh, Félicia; Wever, Renske; Flatz, Lukas; Eggermont, Alexander; et al.
Abstract: Purpose: Patients with cutaneous melanoma stage I/IIA disease are currently not eligible for adjuvant therapy, despite their risk for relapses and death. This study validates the ability of a model combining clinicopathologic factors with gene expression profiling (CP-GEP) to identify patients at high risk for disease recurrence in stage I/II and subgroup stage I/IIA. Patients and methods: 543 patients with stage I/II primary cutaneous melanoma from the University of Tuebingen diagnosed between 2000 and 2017 were analysed. All patients received sentinel lymph node biopsy (SLNB). Analysis was conducted for a separate group of 80 patients who did not undergo SLNB. Results: CP-GEP stratified 424 stage I/IIA patients (78% of the cohort) according to their risk for recurrence, with five-year relapse-free survival (RFS) rates of 77.8% and 93% for CP-GEP high risk (195 patients) and low risk (229 patients), respectively, and hazard ratio of 3.53 (p-value <0.001). In patients who did not receive SLNB biopsy, CP-GEP captured 6 out of 7 relapses. Conclusion: CP-GEP can be used to identify primary cutaneous melanoma patients with a high risk for disease recurrence – especially for stage I/IIA, who are considered low risk by AJCC 8th. These patients may benefit from adjuvant therapy. Also, in the future, when SLNB may become irrelevant, CP-GEP may serve as a risk stratification tool. Highlights: CP-GEP can identify patients with stage I/II melanoma at high risk for recurrence. Five-year RFS rates were 77.8% for CP-GEP high risk and 93% for CP-GEP low risk. In stage I/IIA (RFS rate 86%), CP-GEP identifies high-risk patients (five-year RFS 78%). CP-GEP also shows potential to replace SLNB in patients who did not undergo SLNB.